Drug treatment of type 2 diabetes: Its cost is significantly associated with HbA1c levels. Issue 4 (21st March 2019) - Elgart, Jorge F.; Silvestrini, Constanza; Prestes, Mariana; Gonzalez, Lorena; Rucci, Enzo; Gagliardino, Juan J.
Abstract: Aims: To examine the relationship between costs of hyperglycaemia drug treatment and glycemic control amongst people with type 2 diabetes (T2D). Methods: This observational study utilised data from the QUALIDIAB database on 3, 452 T2D patients seen in Diabetes Centers in Argentina. Patients were classified according to their HbA1c value into two groups: on target (OT; HbA1c ≤ 7%), and not on target (NOT; HbA1c > 7%); within each category we considered clinical and metabolic indicators, as well as type of hyperglycaemia treatment. Monthly expenditure on drugs was estimated by micro‐costing. Multivariable regression analysis was used to evaluate the association between cost of hyperglycaemia treatment and HbA1c values. Results: In total, 48.9% of the participants have HbA1c OT values. Overall monthly per capita costs of this treatment increased significantly (134%) in the NOT group. Multivariable regression analysis showed that expenditure for hyperglycaemia drugs treatment was significant associated with glycemic control (OR: 0.705), diabetes duration (OR: 1.017), systolic blood pressure (OR: 1.006) and treatment of T2D (OR: 2.622). Conclusions: HbA1c NOT significantly increases drugs monthly cost of hyperglycaemia treatment in people with T2D in a country with an emerging market economy.